Tilt training as a treatment for reflex syncope: a multimodal approach!? - Hornikx, Miek; Haemers, Peter; Stans, Linda; Robyns, Tomas; Garweg, Christophe; Ector, Joris; Vandenberk, Bert; Willems, Rik (Frontiers in Neuroscience, 2024)
PurposeReflex syncope is a burdensome disease with considerable repercussions on the quality of life. Tilt training is a therapeutic option, but evidence on this topic is scarce and outdated. Hyperventilation is oftentimes associated with reflex syncope. This study aimed to evaluate the effectiveness of tilt training in patients with reflex syncope and study the association between reflex syncope and hyperventilation.MethodsPatients referred for tilt training after a positive tilt test from July 2014 to March 2021 were included in a single-center, retrospective registry. Demographic characteristics and outcomes of the program were collected. The response of tilt training on (pre)syncope recurrence and the association with hyperventilation were studied.ResultsA total of 173 patients were included. The median age was 27 [17–48] years. Patients needed 2 [1–3] sessions to reach the first negative tilt training. The tilt training program was successfully completed by 65% of patients. An additional 3% reported no complaints in daily life, despite remaining symptomatic during tilt training. Another therapy was initiated in 10% of patients, while 21% dropped out of the tilt training. Presyncope recurred in 21% of patients during a follow-up period of 21 months [16–23]. Concomitant hyperventilation was suspected in 24%. Among these patients, 74% were referred for a hyperventilation provocation test, which confirmed the diagnosis in 82%.ConclusionWe report a reasonable success of tilt training in a contemporary cohort of patients. In patients completing the tilt training program, presyncope, and syncope recurrence was low. Concomitant hyperventilation seems prevalent in patients with reflex syncope and warrants specific attention and treatment.